Rapid influenza diagnostic test at triage can decrease emergency department length of stay - Tsutomu Iwasaki; Toru Hifumi; Kuniyoshi Hayashi; Norio Otani; Shinichi Ishimatsu (Journal of the American College of Emergency Physicians Open, 2020)
Abstract Objective Even if performing rapid influenza diagnostic tests test will not change clinical decision making, we sometimes perform at triage to reduce length of stay in Japan. Whether performing rapid influenza diagnostic tests at triage may shorten emergency department (ED) length of stay (LOS) is remains unclear. We aimed to determine the utility of rapid influenza diagnostic tests at triage in shortening ED length of stay LOS. Methods We retrospectively reviewed medical records of patients discharged from our ED after receiving results from rapid influenza diagnostic tests during the influenza season from December, 2013 to March, 2019. Eligibility criteria were a walk‐in visit, age ≥15 years, triage performed, rapid influenza diagnostic test administered, and no admission. The triage group received rapid influenza diagnostic tests at triage. The after‐examination group received their tests only after examination by a doctor. The primary outcome was ED LOS after propensity score matching to adjust for several covariates. Results Of 2,768 eligible patients, 2,554 patients were enrolled in the triage group (n = 363) or after examination group (n = 2,191). There were 329 matched pairs after propensity score matching. Median ED LOS was significantly shorter in the triage group than in the after‐examination group after propensity score matching (81 min (interquartile range [IQR] 60 to 111) vs 106 min (IQR 80–142); median difference 24 min (95% confidence interval 17–30)). Conclusions Performing rapid influenza diagnostic tests at triage was associated with shorter ED LOS during the influenza season.